School asset management system - Noor Hartini, Shamsudin (2012)
Asset item devided two categories,inventory and model asset.At the school stationeries are used very commonly by people in an office.SAMS is a system from manual to computerized system.It is developed for staffs of the school to take any asset item such as stationeries they need and management of items at the school.Current practice use manual forms of log books to keep records of stationeries taken by staffs.This method burdens staffs who want to take stationeries from school counter.SAMS was the solution to this problem.This system can help staffs in the SK USJ20 manage the procedure of taking stationeries because one of the objectives of this project is to computerized the manual form asset stationeries item taken by staffs. Therefore, this system is will be very helpful and can make the management of asset stationeries item run smoothly. SAMS is developed by using Adobe Dreamweaver CS3 and Xampp Server.